2013
DOI: 10.1159/000350075
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Cholecystokinin-Induced Depolarization of Pacemaking Activity in Cultured Interstitial Cells of Cajal from Murine Small Intestine

Abstract: Background/Aims: In this study, we studied the effects of cholecystokinin (CCK) on pacemaker potentials in cultured interstitial cells of Cajal (ICCs) from mouse small intestine using the whole cell patch clamp technique. Methods: ICCs are pacemaker cells that exhibit periodic spontaneous depolarization, which is responsible for the production of slow waves in gastrointestinal smooth muscle, and generate periodic pacemaker potentials in current-clamp mode. Results: Exposure to CCK (100 nM-5 µM) decreased the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 1,160 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…In addition, ICCs mediate inhibitory and excitatory signals from the enteric nervous system to smooth muscle [25][26][27], and evidence indicates that endogenous agents, such as, neurotransmitters, hormones, and paracrine substances, modulate GI tract motility by influencing ICCs [28][29][30][31]. Furthermore, it has been shown that the pacemaker activities of ICCs in the murine small intestine are mainly due to periodic activations of nonselective cation channels (NSCCs) [32,33] or Cl -channels [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ICCs mediate inhibitory and excitatory signals from the enteric nervous system to smooth muscle [25][26][27], and evidence indicates that endogenous agents, such as, neurotransmitters, hormones, and paracrine substances, modulate GI tract motility by influencing ICCs [28][29][30][31]. Furthermore, it has been shown that the pacemaker activities of ICCs in the murine small intestine are mainly due to periodic activations of nonselective cation channels (NSCCs) [32,33] or Cl -channels [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Smooth muscle cells respond to slow wave depolarization by activating L-type Ca 2+ channels [46]. In addition, smooth muscle response is regulated by neural inputs, and both excitatory and inhibitory enteric motor neurons are closely associated with ICC [14]. Thus, ICC play an important role in the determination and regulation of GI motility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the loss of ICC is implicated in several motility disorders, which suggests that ICC play an important role in the regulation of GI motility [13]. In addition, evidence indicates that endogenous agents, such as, neurotransmitters, hormones, and paracrine substances, modulate GI tract motility by influencing ICC [14]. It has been shown that the pacemaker activities of ICC in the murine small intestine are mainly due to periodic activations of nonselective cation channels (NSCCs) [15,16] or Cl - channels [17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it has been proposed that TRPM7 and ANO1 is responsible for the pacemaker activity in ICCs and may be considered the potential targets for the pharmacological treatment of GI motility disorders. The absence of ICCs in GI tract causes abnormally slow electrical waves and reduces smooth muscle cell contractility and intestinal transit [25] and ICCs also mediate or transduce inputs from the enteric nervous system [28]. Therefore, ICCs play an important role in the determination and regulation of GI motility.…”
Section: Introductionmentioning
confidence: 99%